Fiscal Deficits, Financial Fragility, and the Effectiveness of Government Policies - Markus Kirchner; Sweder van Wijnbergen (Tinbergen Institute, 2012)
Recent macro developments in the euro area have highlighted the interactions between fiscal policy, sovereign debt, and financial fragility. We take a structural macroeconomic model with frictions in the financial intermediation process, in line with recent research, but introduce asset choice and sovereign debt holdings in the portfolio of banks. Using this model, we emphasize a new crowding-out mechanism that works through reduced private access to credit when banks accumulate sovereign debt under a leverage constraint. Our results show that, when banksinvest a substantial fraction of their assets in sovereign debt, the effectiveness of fiscal stimulus policies may be impaired because deficit-financed fiscal expansionsmay tighten financial conditions to such an extent that private demand is crowded out. We also analyze the macroeconomic effectiveness of liquidity supportto commercial banks through recapitalizations or loans by the government and the impact of different ways of financing those policies.
Keywords: E44; E62; H30; 330; Financial intermediation; Fiscal policy; Sovereign debt; Finanzpolitik; Haushaltsdefizit; Öffentliche Schulden; Öffentliche Anleihe; Verdrängungseffekt; Kreditgeschäft; Privatwirtschaft; Finanzintermediation; Theorie